Complete mitochondrial genomes from transcriptomes: assessing pros and cons of data mining for assembling new mitogenomes - Forni, Giobbe; Puccio, Guglielmo; Bourguignon, Thomas; Evans, Theodore; Mantovani, Barbara; Rota-Stabelli, Omar; Luchetti, Andrea (Scientific reports, 2019)
Thousands of eukaryotes transcriptomes have been generated, mainly to investigate nuclear genes expression, and the amount of available data is constantly increasing. A neglected but promising use of this large amount of data is to assemble organelle genomes. To assess the reliability of this approach, we attempted to reconstruct complete mitochondrial genomes from RNA-Seq experiments of Reticulitermes termite species, for which transcriptomes and conspecific mitogenomes are available. We successfully assembled complete molecules, although a few gaps corresponding to tRNAs had to be filled manually. We also reconstructed, for the first time, the mitogenome of Reticulitermes banyulensis. The accuracy and completeness of mitogenomes reconstruction appeared independent from transcriptome size, read length and sequencing design (single/paired end), and using reference genomes from congeneric or intra-familial taxa did not significantly affect the assembly. Transcriptome-derived mitogenomes were found highly similar to the conspecific ones obtained from genome sequencing (nucleotide divergence ranging from 0% to 3.5%) and yielded a congruent phylogenetic tree. Reads from contaminants and nuclear transcripts, although slowing down the process, did not result in chimeric sequence reconstruction. We suggest that the described approach has the potential to increase the number of available mitogenomes by exploiting the rapidly increasing number of transcriptomes.
Keywords: transkriptom; sekvence nukleotidů; data mining; fylogeneze; High-Throughput Nucleotide Sequencing; anotace sekvence; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Transcriptome; sekvenování transkriptomu; reprodukovatelnost výsledků; Isoptera; Reproducibility of Results; genom mitochondriální; Genome, Mitochondrial; Animals; Data Mining; zvířata; vysoce účinné nukleotidové sekvenování; Molecular Sequence Annotation; Base Sequence; RNA-Seq